Oral Cancer Knowledge, Practices, and Attitudes: A Survey of Libyan Dentists - Areej El-Sallak; Werfalli, Sumeia; Gaber, Amal; Shukree Benamar, Manal (Libyan Journal of Dentistry, 2023)
Dentists play an important role in early detection of oral cancerous lesions. several studies indicate that dentists lack knowledge in oral cancer etiology and diagnosis. Role in the control studies assessing dentists' oral cancer awareness in Libya are lacking. Objectives: This study examined the oral cancer awareness and practice among dentists in Libya. Materials and methods: : Administered questionnaires were distributed on dentists working in private and public clinics in the city of Benghazi. Participants’ responses to the questionnaire were analyzed using descriptive and analytical statistics. Results: Three hundred dentists returned completed questionnaires; 237 (79%) females and 63 (21%) males and most of them were under 40 years old 227 (75.7%). Although most dentists were knowledgeable about the most common site, type, and screening method of oral cancer, only about half of the dentists were aware of tobacco as the main risk factor and biopsy as the most proper diagnostic technique for oral cancer. Despite that 86% of the dentists reported that they perform mucosal examination as part of their routine dental examination, about half of the dentists reported lack of confidence in detecting oral cancer and most dentists expressed need for further education and training in this area. Conclusion: Overall, this study highlighted the importance of introducing continuous education and training programs to dentists which could increase oral cancer prevention and survival rates among oral cancer patients.